When Jessie came across the sea - Hest, Amy; Lynch, Patrick James; Scholastic Inc. (New York : Scholastic Inc., 1999)
A thirteen-year-old Jewish orphan reluctantly leaves her grandmother and immigrates to New York City, where she works for three years sewing lace and earning money to bring Grandmother to the United States, too.
Includes half title page.
Keywords: Emigration and immigration -- Juvenile fiction; Jews -- Juvenile fiction; Orphans -- Juvenile fiction; Grandmothers -- Juvenile fiction; Emigration and immigration -- Fiction; Jews -- Fiction; Orphans -- Fiction; Grandmothers -- Fiction; Emigration and immigration; Grandmothers; Jews; Orphans; Novels; Fiction; Juvenile works; Novels